2008
DOI: 10.1161/strokeaha.107.510875
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Health Policy 2007

Abstract: N otable advances have been made in stroke policy and outcomes research over the past year. Policy-relevant gray and published research is included in this review. The advances selected are organized under 3 areas: stroke policy and related evidence, predictive modeling, and quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…There have been clear advances in hospitalized stroke care to address acute symptoms; however, there remains a lack of focus on post-stroke interventions that address psycho-social symptoms, including the manifestation of depression and stress that may hinder social and workforce participation (Lyons, Rudd, & Alvaro, 2007). A literature review conducted by Murray, Young, Forster, and Ashworth (2003) revealed that the most common long-term problem identified by stroke patients and their carers was lack of emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…There have been clear advances in hospitalized stroke care to address acute symptoms; however, there remains a lack of focus on post-stroke interventions that address psycho-social symptoms, including the manifestation of depression and stress that may hinder social and workforce participation (Lyons, Rudd, & Alvaro, 2007). A literature review conducted by Murray, Young, Forster, and Ashworth (2003) revealed that the most common long-term problem identified by stroke patients and their carers was lack of emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…Signifi cant advances have been made in acute care for stroke and in primary and secondary prevention, but long-term outcome and its determinants remain neglected [6,36]. Lack of funding for rehabilitation research and changes in reimbursement that limit time in rehabilitation continue to negatively affect further development and implementation of new approaches and techniques.…”
Section: Health Care Policy and Stroke Rehabilitationmentioning
confidence: 99%
“…Rehabilitation techniques involving massed, repetitive practice have consistently shown superior functional outcomes to standard physiotherapy approaches [5]. Sadly, widespread clinical implementation of these approaches remains limited due to defi ciencies in health care policy, defi ciencies in health services delivery, and lack of education, reimbursement, and time [6,7].…”
Section: Introductionmentioning
confidence: 99%